An experience of thought in act. Art as a «problem» (Nóema, 2017)
This text aims to describe an experience,  maybe an experience of the thought as a spiritual act. This writing is both the testimony of a restless night and the arrival of a sudden intuition…of many other nights and many other intuitions. It is about the incessant questions connected to the nature of the art. It is about the interrogations that call into question the experience of the art. The main question, at the end, is always the same: when we refer to an aesthetic experience, what are we really talking about? And what kind of relation takes place when we are dealing with a work of art? Finally, how can we determine the categories of “quality” and “quantity” with regard to an experience that, albeit enigmatic, we can still define as an aesthetic one?
Keywords: experience; art; quality; quantity; question; testimony; work; intuition; relation; spiritual act